Public Response to MUI Fatwa No. 83 of 2023: Social Implications in Makassar, South Sulawesi - Hawalay, Humaerah; Ramli, Arif Rahman; Handayani, Dwi (Parewa Saraq: Journal of Islamic Law and Fatwa Review, 2024)
This study examines public responses to MUI Fatwa No. 83 of 2023, which prohibits transactions with Israeli-affiliated products and emphasizes support for Palestine. The research aims to bridge the knowledge gap regarding how communities understand and implement the fatwa, while also exploring its potential social and political consequences. A qualitative methodology was employed, utilizing observation, interviews, and documentation as data collection techniques. The data sources include primary and secondary materials relevant to the fatwa and its community impact. The findings reveal that the community in Manggala Sub-district understands and accepts the fatwa’s principles. They view it as an essential step in showing solidarity with Palestine, often expressing support through joint prayers, fundraisers, and adherence to the prohibition of Israeli products. Practical implementations of the fatwa, such as organized charity activities, demonstrate a significant level of community engagement.  This research is original in its focus on a localized response to MUI Fatwa No. 83 of 2023, contributing to a broader understanding of the social dynamics surrounding Islamic legal directives. The implications highlight the need for enhanced and sustainable education programs to socialize fatwas effectively. Local governments and the MUI should collaborate to provide direct counseling, community leader training, and support mechanisms for traders to adapt without economic disruption. By addressing these aspects, the study underscores the importance of aligning religious directives with practical societal needs.